2013
DOI: 10.1097/jfn.0b013e31828badfa
|View full text |Cite
|
Sign up to set email alerts
|

With Care and Compassion

Abstract: In this study, we conducted in-depth qualitative interviews with 20 adolescent sexual assault patients aged 14-17 years who sought postassault medical forensic examinations at one of two Midwestern Sexual Assault Nurse Examiner programs. Our goals were to examine how adolescent victims characterized the quality of the emotional/interpersonal care they received and to identify specific aspects of Sexual Assault Nurse Examiner nursing practice that were helpful and healing. Overall, the patients had very positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Of the 107 papers included in the review, some were relevant to more than one of our three review questions. For review question one, we included 78 publications providing information on how sexual assault services address mental health and substance misuse [20, 24-26, 33-106]; for review question two, we included 6 papers of five trial evaluations [84,89,92,[107][108][109]; and for review question three, we included 34 studies on stakeholders' views [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] and 10 policy documents [20,22,[127][128][129][130][131][132]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 107 papers included in the review, some were relevant to more than one of our three review questions. For review question one, we included 78 publications providing information on how sexual assault services address mental health and substance misuse [20, 24-26, 33-106]; for review question two, we included 6 papers of five trial evaluations [84,89,92,[107][108][109]; and for review question three, we included 34 studies on stakeholders' views [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] and 10 policy documents [20,22,[127][128][129][130][131][132]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We found 34 papers [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] relating to 32 studies, which reported stakeholders' views on how sexual assault services should identify and respond to mental health and substance misuse problems for people following sexual assault. Twenty five were peer-reviewed publications [25,34,44,53,54,60,72,78,82,90,94,[110][111][112][113][114]…”
Section: Q3: Studies On Stakeholders' Viewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Australian researchers found that mental health workers responding to survivors had not had adequate SA training and rarely referred women to mental health professionals specializing in SA recovery (McLindon & Harms, 2011). On the other hand, adolescent SA victims reported positive experiences with well-trained SA Nurse Examiners (SANEs) (Campbell, Greeson, & Fehler-Cabral, 2013). Although promising, research has yet to investigate women’s positive and negative experiences with mental health professionals after disclosing SA in their own words (Campbell, Dworkin, & Cabral, 2009).…”
mentioning
confidence: 99%